Plant-based scaffolds and osteogenesis: a systematic review - Hashmat Gul; Kunza Naveed Asdaq; Muhammad Kaleem; Muhammad Hashim Malik (Journal of the Pakistan Medical Association)
Objective: To enhance the understanding and usefulness of decellularised plant tissues as scaffolds for bone tissue engineering, and to review the recent advances in plant-based scaffolds for bone regeneration.